Gender Differences in Transport Behaviour Patterns - Lejsková, Pavla; Pojkarová, Kateřina; Kudláčková, Nina; Becková, Helena; Čubranić-Dobrodolac, Marjana (My University, 2023)
Gender equality is a topical issue that also concerns the transport sector. Gender-neutral transport systems may not be equally suitable for each gender and thus fail to meet their mobility requirements. Therefore, there is a need to study the transport behaviour of men and women and use the findings to further develop transport systems. This article focuses on gender differences in transport behaviour patterns. To obtain the necessary data, a survey was conducted through a structured personal questionnaire. The results were then processed using selected statistical methods. The results of the survey show that the differences are mainly in the means of transport used or the purposes of the trips. On the other hand, as for the criteria that influence the selection of a mode of travel, time is equally important for both women and men, followed by the purpose of the journey and the availability of transport. The survey thus confirmed that there are significant differences in the transport behaviour of men and women.
Genderové rozdíly ve vzorcích dopravního chování
Keywords: Gender differences; transport; mobility; transport behaviour; Genderové rozdíly; doprava; mobilita; dopravní chování